Development priorities for African universities. (1st November 2015) - Baijnath, Narend; James, Genevieve
African knowledge remains at best on the margins, struggling for an epistemological foothold in the face of an ever dominant Western canon. At worst, African knowledge is disparaged, depreciated, and dismissed. It is often ignored even by African scholars who, having gained control of the academy in the postcolonial context, seemingly remain mesmerized by the Western canon in most dimensions of thought, inquiry, theorization, culture (classical as well as popular), and ideology. Such is the hegemonic influence of historical legacy and current power relations in the production and dissemination of knowledge. This paper argues that African knowledge, given appropriate impetus, can serve as a powerful stimulus to development. Against the backdrop of intractable development challenges, the paper will explore the role of African universities in the creation, dissemination, and support of African knowledge; and the preservation of indigenous knowledge. Since a scholarly effort towards integrating an African ethos into discourse, consciousness, and praxis is critical, this paper will consider transformative action for African human development and outline key priorities for African universities to position African knowledge for successful development effectively, and thereby provide an alternative canonical perspective more resonant with the aspirations, interests, and development agenda of the continent.